Priority Needs for the Internal Quality Assurance Operations of Schools under Nakhon Si Thammarat Primary Educational Service Area Office 2 - Thenwong, Kritnara; Pechpuang, Sopon; Autchobkarn, Sutkhanueng; Rak-ngam, Chaipot (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to investigate the current situation, the desired situation, and the priority needs for implementing internal quality assurance in schools, to compare the priority needs for implementing internal quality assurance in schools in relevance to gender, educational level, work experience, position, and school size, and to identify problems and suggestions related to the implementation of internal quality assurance in schools. The sample consisted of 275 school personnel, including administrators and heads of work groups from schools under Nakhon Si Thammarat Primary Educational Service Area Office 2, selected through cluster random sampling, with schools as the clusters. The data collection instrument was a five-point rating scale questionnaire with a consistency index ranging from .80 - 1.00 and the overall alpha coefficient of .961. The data analysis statistics included mean, standard deviation, Priority Needs Index, One-way ANOVA, and multiple comparisons using the LSD method. The findings revealed that: 1) the current and desired situation of implementing internal quality assurance in schools were at good and very good levels, respectively, and the priority needs for implementing internal quality assurance in schools revealed that the greatest need was for the evaluation and assessment of educational quality 2) the overall comparison of priority needs for implementing internal quality assurance in schools as perceived by personnel in relevance to their educational level, work experience, and school size showed no significant differences. When considered by individual aspect, it was found that, based on the gender variable, male personnel had a significantly higher perception of priority needs in the aspect of implementing the educational development plan than female personnel, at .05 level. Based on the position variable, personnel holding administrative positions had a significantly higher perception in the aspect of setting educational standards than those in head of work group positions, at .05 level. 3) Problems and suggestions indicated that some personnel have still lacked knowledge and understanding of the internal quality assurance system and processes, and there was a lack of supervision and evaluation. Therefore, administrators should hold meetings to clarify with the stakeholders, which provide opportunities for all parties to participate in setting educational standards, conducting evaluations, and assessing educational quality so that internal quality assurance can be implemented more effectively in line with the school’s standards.